Stakeholder Engagement in Sport Policy Decision Making in Taiwan during the COVID-19 Pandemic. Issue 7 (18th October 2021) - Henry, Ian; Kao, Chin-Hsung; Ko, Ling-Mei
Abstract: This paper focuses on the salience, engagement and influence of selected stakeholders in two key sport policy initiatives in Taiwan during the Covid-19 pandemic. The paper identifies three principal dimensions in the stakeholder literature which relate to, the uses of stakeholder theory; sources of nature and level of stakeholder influence; and perspectives on the nature of stakeholder decision-making; and it seeks to evaluate the contribution of these three principal dimensions of stakeholder theory to the explanation of stakeholder resources, interests, and behaviour in the policy/management scenarios identified. In terms of methodology the study is founded on the ontological and epistemological assumptions of critical realism. In terms of method, the analysis of stakeholder interests, activities and impacts is undertaken through a thematic analysis of documents, and interviews with leading figures in government and sport in Taiwan (n = 11), in relation to the two policy initiatives highlighted. The paper explores the outcomes of stakeholder interaction in the two scenarios, and evaluates the contribution to our understanding of these outcomes, providing a useful test of the extent to which the cases in the two scenarios respectively depart from, or conform to, the outcomes anticipated in the ideal typical accounts of stakeholder interaction.